HIGH-FIELD MAGNETORESISTANCE OSCILLATIONS IN ALPHA-[BIS(ETHYLENEDITHIO)TETRATHIAFULVALENE]2KHG(SCN)(4) - THE EFFECTS OF MAGNETIC BREAKDOWN, EXCHANGE INTERACTIONS, AND FERMI-SURFACE REORDERING - Caulfield, J; Blundell, S; Dejongh, M; Hendriks, P; Singleton, J; Doporto, M; Pratt, F; House, A; Perenboom, J; Hayes, W; Kurmoo, M; Day, P (1995)
High-field magnetoresistance measurements have been performed on single-crystal samples of the charge-transfer salt α-ET2KHg (SCN)4 [where ET is bis(ethylenedithio)tetrathiafulvalene] using fields of up to 30 T. We examine the character of the Shubnikov-de Haas oscillations for a range of samples, temperatures, and field regimes to understand the role played by spin splitting and magnetic breakdown effects. Angle-dependent magnetoresistance oscillations (AMRO) in magnetic fields below the kink transition (22 T) indicate that the low-magnetic-field band structure is dominated by a one-dimensional (1D) open section of Fermi surface (FS) inclined at ∼21°to the crystallographic b*c plane; above the kink, the AMRO change in character, indicating that the FS now possesses a 2D closed section in the form of a distorted cylinder. The data are discussed in terms of a recent model of the low-field band structure and give definitive proof that the kink is the signature of a magnetic-field-induced change in the FS. © 1995 The American Physical Society.